Preparation of the Magnesium Hydroxide-Activated Carbon Composites and Optimize of Their Decolorization Process for Syrup - Jinzu CHEN; Xiaowen WEI; Jingjing NONG; Lifang HAN; Xue FENG; Tingfan TANG; Lijun LI; Hao CHENG (Shipin gongye ke-ji)
In this study, magnesium hydroxide-activated carbon composites were prepared by in-situ generation of magnesium hydroxide deposited on the surface of activated carbon to find green and environmentally friendly syrup decolorization material with high adsorption. These composites were characterized by scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), specific surface area and porosity analyzer (BET) and X-ray diffraction (XRD). Besides, the optimal decolorization of remelt syrup of brown granulated sugar was optimized by single factor and orthogonal experiments with the decolorization rate as the index, and the input amount, pH, decolorization temperature and decolorization time of the composites as the influencing factors. The results showed that the prepared composites were porous, with large specific surface area and porosity, sound crystal structure and strong adsorptive capacity. The decolorization rate could reach 80.7% under the optimal process of syrup decolorization as: 0.70 g composite material, pH 10.00, 50 ℃ decolorization temperature and 50 min decolorization, of which the decolorization effect was significantly better than that of commercial activated carbon. The above indicates that magnesium hydroxide-activated carbon composites have an ideal decolorization effect on syrup, and present certain application prospects as a green material in the sugar industry.